Mewujudkan Generasi Bebas Polio: Program Sub PIN Polio Di Puskesmas Mojolangu Kota Malang - Yuni Asri; Dian Pitaloka Priasmoro; Sahda Eka Ardiyanti; Trian Lutfianti; Camelia Finda Arisanti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The eradication of polio has become a global priority. Through the synchronized Sub-PIN Polio immunization program, the aim is to enhance human welfare and achieve a polio-free generation. The target is to reach 95% immunization coverage in the Mojolangu Health Center, Malang City. Immunization activities in the Mojolangu Health Center's area cover several schools, integrated health posts (Posyandu), and early childhood education centers (Pos PAUD), targeting children aged 0-7 years. The first round took place from January 15th to 20th, 2024. The immunization coverage has reached the target, with 95.3% of children vaccinated. This synchronized immunization effort aligns with the vision of a polio-free generation and sustainable community health achievement.